The Impact of Lockdown During the COVID-19 Outbreak on Dietary Habits in Various Population Groups: A Scoping Review - Bennett, Grace; Young, Elysia; Butler, Isabel; Coe, Shelly (Frontiers in Nutrition, 2021)
Since the beginning of COVID-19, access to fresh food has been restricted with more time inside and limited physical activity. However, more time at home may have resulted in positive habits including increased cooking. The aim of this review was to assess dietary changes during the first lockdown. Themes and patterns were considered and associations with other lifestyle factors were assessed. Methods: Between June and July 2020, Pubmed, Google Scholar and Science Direct databases were searched, and results were screened for eligibility based on title and abstract, and full text. The inclusion criteria of this search included: papers published in the year 2020; studies that investigate the impact of COVID-19 lockdown on diet; papers published in English. Exclusion criteria were as follows: papers examining dietary changes in those following a structured diet based on diagnosed conditions or dietetic advice; literature, systematic or narrative studies reviewing previous research. Researchers agreed on study characteristics for extraction from final papers. Results: 4,322 studies were originally considered with 23 final full text papers included. Four themes were identified: dietary patterns, dietary habits (favourable), dietary habits (unfavourable), other (includes physical activity levels, weight gain). A total of ten studies reported an increase snacking behaviour, while six studies found that participants increased their meal number and frequency during quarantine. Eleven studies reported favourable changes in dietary habits with an increase in fresh produce and home cooking and reductions in comfort food and alcohol consumption. However, nine studies found a reduction in fresh produce, with a further six reporting an increase in comfort foods including sweets, fried food, snack foods and processed foods. Two studies reported an increase in alcohol consumption. In eight studies participants reported weight gain with seven studies reporting a reduction in physical exercise. Conclusion: The effect of COVID-19 both negatively and positively impacted dietary practices throughout Europe and globally, and the negative diet habits were associated with other poor lifestyle outcomes including weight gain, mental health issues and less physical activity. Both in the short term and if sustained long term, these changes may have significant impacts on the health of the population.